Implementasi Building Information Modeling (BIM) Pada Konstruksi High Risk Building - Akbar, Mochammad Nuril Faizal; Winanda, Lila Ayu Ratna; Manaha, Yosimson Petrus (Universitas Batanghari Jambi, 2025)
Almost all construction companies in Indonesia use conventional methods in planning, including volume analysis. The weakness of the conventional method is that it requires more time with low precision. The need for updating the implementation to the planning results is also difficult to do. Therefore, the purpose of this research is to implement Building Information Modeling (BIM), which is a method to display virtual construction before physical construction begins, based on the Autodesk Revit application. Analysis using the Autodesk Revit application automatically generates a work volume of 4,333,885m³ for concrete work and 666,338.61kg for reinforcement work in the case under review. The results of the analysis show that the application of Building Information Modeling (BIM) in construction projects can simplify and accelerate the design process.